Analisis Kesenjangan antara Harapan dan Pelayanan yang Diterima Terkait Informasi di Instalasi Rawat Inap RSUD Haji Makassar - Idarwati Mustafa; Khaeriah B; Andi Mikhrunnisai (Lentera Pena Cendekia, 2025)
The quality of healthcare in a patient-centered care model heavily depends on patients’ perceptions, with the provision of clear information being a critical component. Gaps between patients’ expectations and the actual information received often lead to dissatisfaction and decreased trust in healthcare providers. This study aimed to analyze the gap between patients’ expectations and the services received regarding information provision in the Inpatient Unit of RSUD Haji Makassar. This observational study employed a cross-sectional design. The study population consisted of all inpatients in 2015, and a total of 98 respondents were selected using quota sampling. Data were analyzed univariately, and the Importance Performance Analysis (IPA) method was applied to map priority areas for service quality improvement based on the comparison between expectations and performance. The average alignment between patients’ expectations and the services received was relatively high, at 93.83%. Nurse communication performance (95.47%–96.43%) was found to be more optimal compared to the information provided by doctors (91.88%–93.35%). Based on the IPA analysis, the aspects prioritized for immediate improvement (Quadrant I) were doctors’ explanations regarding diagnosis results, treatment risks, and medication side effects. The lowest alignment was observed in doctors’ explanations concerning treatment risks (91.91%). The higher alignment in nursing services can be attributed to nurses’ more frequent contact with patients compared to doctors, who face time constraints and irregular visit schedules. To minimize these gaps, hospital management should enhance doctors’ communication competencies through targeted training, implement structured visit schedules, and strengthen interprofessional collaboration. These strategies are crucial to improving patient safety and maintaining high standards of public healthcare service quality.